2021
DOI: 10.1038/s41598-021-83818-5
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem response persists after a prolonged marine heatwave

Abstract: Some of the longest and most comprehensive marine ecosystem monitoring programs were established in the Gulf of Alaska following the environmental disaster of the Exxon Valdez oil spill over 30 years ago. These monitoring programs have been successful in assessing recovery from oil spill impacts, and their continuation decades later has now provided an unparalleled assessment of ecosystem responses to another newly emerging global threat, marine heatwaves. The 2014–2016 northeast Pacific marine heatwave (PMH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
141
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 161 publications
(148 citation statements)
references
References 92 publications
6
141
1
Order By: Relevance
“…Marine mammals and other taxa have methods of compensating for noise (Parks et al, 2009;Tennessen and Parks, 2016;Fournet et al, 2018a;Matthews et al, 2020) but the effectiveness of compensatory behavior and the ultimate effects of noise on reproductive success are unknown. In marine protected areas and elsewhere, underwater noise is just one of many stressors that affect marine wildlife (Hatch et al, 2012;Williams et al, 2015;Blair et al, 2016;Haver et al, 2019), for example, the recent catastrophic effects of changing climate and unpredictable conditions on Alaska's marine ecosystems (Oliver et al, 2018;von Biela et al, 2019;Piatt et al, 2020;Arimitsu et al, 2021;Suryan et al, 2021). As maritime activities gradually resume in Glacier Bay and other areas, and marine protected area managers must rise to the challenge to use what has been learned in the pandemic-induced quiet to improve methods to mitigate vessel noise and foster healthy marine ecosystems in these vulnerable and important public resources.…”
Section: Discussionmentioning
confidence: 99%
“…Marine mammals and other taxa have methods of compensating for noise (Parks et al, 2009;Tennessen and Parks, 2016;Fournet et al, 2018a;Matthews et al, 2020) but the effectiveness of compensatory behavior and the ultimate effects of noise on reproductive success are unknown. In marine protected areas and elsewhere, underwater noise is just one of many stressors that affect marine wildlife (Hatch et al, 2012;Williams et al, 2015;Blair et al, 2016;Haver et al, 2019), for example, the recent catastrophic effects of changing climate and unpredictable conditions on Alaska's marine ecosystems (Oliver et al, 2018;von Biela et al, 2019;Piatt et al, 2020;Arimitsu et al, 2021;Suryan et al, 2021). As maritime activities gradually resume in Glacier Bay and other areas, and marine protected area managers must rise to the challenge to use what has been learned in the pandemic-induced quiet to improve methods to mitigate vessel noise and foster healthy marine ecosystems in these vulnerable and important public resources.…”
Section: Discussionmentioning
confidence: 99%
“…The extreme MHW impacted marine organisms at multiple trophic levels (Barbeaux et al, 2020;Brodeur et al, 2019;Daly et al, 2017;Peterson et al, 2017;Santora et al, 2020), and a growing body of evidence indicates an abrupt ecosystem-wide response occurred over the large spatial extent (Suryan et al, 2021;Walsh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The extreme MHW impacted marine organisms at multiple trophic levels (Barbeaux et al, 2020; Brodeur et al, 2019; Daly et al, 2017; Peterson et al, 2017; Santora et al, 2020), and a growing body of evidence indicates an abrupt ecosystem‐wide response occurred over the large spatial extent (Suryan et al, 2021; Walsh et al, 2018). Large‐scale mortality events by marine predators and pelagic food web specialists were among the first visible indicators of a major ecosystem perturbation in the GOA during the MHW (Piatt et al, 2020; Savage, 2017) and suggested a major disruption in energy transfer through the middle trophic level.…”
Section: Introductionmentioning
confidence: 99%
“…Between late 2013 and 2016, a marine heatwave occurred in the GOA that exceeded the magnitude and duration of any other heatwave on record in the region. This heatwave event led to temperature anomalies greater than 2.5 • C (Bond et al, 2015;Di Lorenzo and Mantua, 2016) and unprecedented shifts in the region's biological communities, including increases in harmful algal blooms, reductions in fishery recruitment, and mass mortality of marine mammals and seabirds (Leising et al, 2015;Piatt et al, 2020;Suryan et al, 2021). In the summer of 2019, the GOA was impacted by another marine heatwave, leading to similarly extreme temperature anomalies (Amaya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%